Rancang Bangun, Penyerahan, dan Sosialisasi Sistem Informasi Jasa Katering Berbasis Web - Jefri Junifer Pangaribuan; Ilhami, Mirza; Chandra, Wenripin; Romindo, Romindo (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2024)
Catering services are integral to the food and beverage industry, particularly in providing meals for various events such as weddings and corporate functions. However, many catering businesses still rely on outdated, conventional systems that result in inefficiencies and difficulties in reaching potential customers. To address these challenges, this research focuses on developing a modern information system tailored to the needs of catering enterprises. The development process began with the design of a Use Case Diagram, followed by the creation of a user-friendly interface and a robust database structure. The final product is a fully functional website that streamlines the ordering process, enhances customer interaction, and provides a platform for suppliers to effectively promote their products. The system was rigorously tested, and user feedback was gathered through questionnaires. The results indicated a satisfaction rate of 80%, demonstrating that the website meets the users' needs and successfully resolves issues related to service accessibility and promotional outreach. This project highlights the importance of integrating modern technology into traditional business models to improve efficiency and customer satisfaction.